AKSELERASI PENERAPAN APLIKASI SISTEM INFORMASI KEARSIPAN DINAMIS TERINTEGRASI (SRIKANDI) DI BADAN PENGELOLA KEUANGAN DAN ASET DAERAH (BPKAD) PROVINSI RIAU TAHUN 2024 - Cipta, Adhi Dwi; Pane, Rico Purnawandi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
The acceleration of the implementation of the Dynamic Integrated Archival Information System Application (SRIKANDI) at the Regional Financial and Asset Management Agency (BPKAD) of Riau Province represents a response to the demands for rapid national digital archival transformation, which requires swift and effective execution. However, the pace of adoption and digital transformation continues to face various obstacles that hinder the acceleration process. This study aims to analyze the acceleration of SRIKANDI implementation in archival management in 2024. This research employs a qualitative method with a descriptive approach, utilizing data collection techniques such as purposive sampling interviews and documentation. Data analysis is conducted through data presentation, data reduction, data verification, and conclusion drawing. The analysis is based on Indrajit’s e-government theory, which includes the indicators of support, capacity, and value. The findings indicate that although the support aspect has been reinforced by regulatory frameworks and leadership commitment to accelerate implementation, the pace of internal strengthening remains lagging. In terms of capacity, limitations in human resource competencies and technical infrastructure constraints serve as the main barriers to accelerating technology adoption. Meanwhile, the value aspect has not been optimally realized, thereby slowing down the motivation for the accelerated utilization of the system. This study recommends acceleration strategies through intensive capacity building of government personnel, structured and continuous training programs, and the rapid optimization of SRIKANDI utilization within bureaucratic work processes to achieve the expected acceleration of digital transformation. Keywords: Acceleration, Implementation, SRIKANDI.